2010
DOI: 10.1007/s11661-009-0142-5
|View full text |Cite
|
Sign up to set email alerts
|

Austenite Nucleation and Growth Observed on the Level of Individual Grains by Three-Dimensional X-Ray Diffraction Microscopy

Abstract: Austenite nucleation and growth is studied during continuous heating using three-dimensional X-ray diffraction (3-D XRD) microscopy at the European Synchrotron Radiation Facility (ESRF) (Grenoble, France). Unique in-situ observations of austenite nucleation and growth kinetics were made for two commercial medium-carbon low-alloy steels (0.21 and 0.35 wt pct carbon with an initial microstructure of ferrite and pearlite). The measured austenite volume fraction as a function of temperature shows a two-step behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 24 publications
0
28
1
1
Order By: Relevance
“…Therefore, the transition from the zone of fast austenite formation (S1) to the zone of slow austenite formation (S2) is rather smooth. A somewhat sharp transition has been reported in dilatometric experiments of austenite formation during the continuous heating of annealed ferrite-pearlite microstructure [16,17] under heating rates from 1 °C/s to 200 °C/s. One could thus conclude that the cold-rolling of the ferrite-pearlite initial microstructure is enhancing the spheroidization of cementite, which has an impact on the formation of austenite in samples heated at 150 °C/s.…”
Section: Austenite Growth Into Pearlitementioning
confidence: 65%
See 2 more Smart Citations
“…Therefore, the transition from the zone of fast austenite formation (S1) to the zone of slow austenite formation (S2) is rather smooth. A somewhat sharp transition has been reported in dilatometric experiments of austenite formation during the continuous heating of annealed ferrite-pearlite microstructure [16,17] under heating rates from 1 °C/s to 200 °C/s. One could thus conclude that the cold-rolling of the ferrite-pearlite initial microstructure is enhancing the spheroidization of cementite, which has an impact on the formation of austenite in samples heated at 150 °C/s.…”
Section: Austenite Growth Into Pearlitementioning
confidence: 65%
“…The change in cementite morphology is thought to be related to the change in austenite distribution in the matrix, as described in Section 3.1. When the cementite morphology in pearlite still remains mainly lamellar, as in samples heated at 1500 °C/s, the formation of austenite takes place quickly in the pearlite regions [16,17]. A banded mixture of ferrite and austenite (martensite) is thus observed in the final microstructure (cf.…”
Section: Austenite Growth Into Pearlitementioning
confidence: 99%
See 1 more Smart Citation
“…Austenite formation in low carbon steels has been studied extensively in the literature starting from different microstructures [4][5][6]. Previous work has shown that in ferritic-pearlitic microstructures the formation of austenite was described as taking place in three main successive steps: (1) nucleation of austenite in pearlite colonies, ferrite-pearlite grain boundaries or ferrite-ferrite grain boundaries, (2) rapid growth of austenite consuming pearlite, (3) slower growth of austenite consuming ferrite [7,8]. Based on the above theory, as for ferrite-pearlite banded microstructure in large forging steel, austenization in ferrite bands and pearlite bands are asynchronous.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is worth mentioning that some new methods have been used for austenite formation study recent years. For example, Savran et al [10] studied the nucleation and growth of austenite from ferrite/pearlite structures using a three-dimensional high-energy X-ray diffraction (3-D XRD) microscope. Additionally, Esin et al [11] investigated the austenitization during both slow and fast heating for different microstructures of a selected low-alloy steel by simultaneously using in situ high-energy synchrotron X-ray diffraction and dilatometry.…”
Section: Introductionmentioning
confidence: 99%